2022
DOI: 10.1038/s41467-022-30486-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically actuated soft heliconical architecture via frequency of electric fields

Abstract: Dynamic electric field frequency actuated helical and spiral structures enable a plethora of attributes for advanced photonics and engineering in the contemporary era. Nevertheless, leveraging the frequency responsiveness of adaptive devices and systems within a broad dynamic range and maintaining restrained high-frequency induced heating remain challenging. Herein, we establish a frequency-actuated heliconical soft architecture that is quite distinct from that of common frequency-responsive soft materials. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Zheng et al recently reported tunable color-based anti-counterfeiting and light encryption of several cholesteric liquid crystal systems. 49–51 Light-induced dynamic helical transformation of chiral photo-switches in cholesteric liquid crystals can control the color tuning, erasing, reversibility, multistability and viewing angle dependence of pre-recorded patterns. These properties lead to digitally controllable, selectable and extractable multistable reflection states that can be used for anti-counterfeiting or encryption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al recently reported tunable color-based anti-counterfeiting and light encryption of several cholesteric liquid crystal systems. 49–51 Light-induced dynamic helical transformation of chiral photo-switches in cholesteric liquid crystals can control the color tuning, erasing, reversibility, multistability and viewing angle dependence of pre-recorded patterns. These properties lead to digitally controllable, selectable and extractable multistable reflection states that can be used for anti-counterfeiting or encryption.…”
Section: Resultsmentioning
confidence: 99%
“…49 Frequency-responsive heliconical LCs have been demonstrated to show reversible modulation of the photonic bandgap over a wide spectral range by delicately combining frequency-dependent thermal effects, field-induced dielectric torque, and elastic equilibrium. 50 They also demonstrated that programmed micro-patterned heliconical structures prepared by local polymer stabilization can be used for anti-counterfeiting applications by controlling the applied electric field to exhibit high color saturation and full color range, including visible light. 51…”
Section: Resultsmentioning
confidence: 99%
“…The device’s transparent state is highly reliant on the electric field or better vertical alignment, and its light-scattering state must be accompanied by intense dye light absorption. The approach of Bragg reflection band control is mainly based on CLC, blue-phase LC, and opal/inverse opal structures, regulating the light reflection band by adjusting the CLC pitch, blue LC lattice structure, and opal structure, respectively. However, these devices did not consider good light-scattering or transparent performance.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the orientational ordering of LCs can be controlled by different boundary geometries [3] and anchoring conditions [4] , allowing the formation of diverse structures or superstructures, including topological defects (i.e., focal conic domains [5] ). These structures exhibit extraordinary sensitivity to various external stimuli, including light, electric field, heat, force, magnetic field, and so on [6][7][8][9] . Thus, there are many degrees of freedom in the way that the structure is coded and the tunability is devised for the design of soft-matter-based devices with innovative functions.…”
Section: Introductionmentioning
confidence: 99%